Choriocarcinoma presenting following a molar pregnancy and preterm vaginal delivery: rarest of rare case - N. R., Sindhu; Shetty, Shraddha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Choriocarcinoma is the aggressive histologic type of GTN and is characterized by vascular invasion and metastases of widespread. Choriocarcinoma metastasizes hematogenously. Suction and evacuation were done on admission. Beta-hCG was 67900 mIU/ml and 144523 mIU/ml on day 1 and day 3 respectively and histopathology showed Choriocarcinoma. This is very unusual case of reviewing sequential events. It was difficult to detect is it new pregnancy or choriocarcinoma. Investigators were biased with high beta-hCG values indicating malignancy. So there was differential diagnosis as choriocarcinoma based on history of molar pregnancy and increasing beta-hCG value and also dictum of ’non molar pregnancy following live birth is always choriocarcinoma. However histopathology report suggested choriocarcinoma and was diagnostic.